2013
DOI: 10.1063/1.4804204
|View full text |Cite
|
Sign up to set email alerts
|

In situ doped phosphorus diffusion behavior in germanium epilayer on silicon substrate by ultra-high vacuum chemical vapor deposition

Abstract: Phosphorus diffusion behaviors in in situ doped germanium epilayers on Si substrate grown in an ultra high vacuum chemical vapor deposition system at 500 °C are investigated. The phosphorus diffusion mechanism during the growth process is dominated by the extrinsic diffusion process, which can be well described with a model including a cubic dependence of diffusivity on the doping concentration. The phosphorus diffusivity into the boron-doped Ge is lower than that into the intrinsic Ge layer by about one order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For the sample annealed at 150 mJ/cm 2 with preannealing, the junction depth is only about 44 nm at the concentration of 1 × 10 18 cm −3 , which is just the same as that in the as-implanted sample. The slight diffusion only occurs in the region with phosphorus concentration above 1 × 10 18 cm −3 , and the diffusivity seems to depend on the dopant concentration, as reported in [7] and [8]. It results in a sharper boxshaped shallow junction.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…For the sample annealed at 150 mJ/cm 2 with preannealing, the junction depth is only about 44 nm at the concentration of 1 × 10 18 cm −3 , which is just the same as that in the as-implanted sample. The slight diffusion only occurs in the region with phosphorus concentration above 1 × 10 18 cm −3 , and the diffusivity seems to depend on the dopant concentration, as reported in [7] and [8]. It results in a sharper boxshaped shallow junction.…”
Section: Methodsmentioning
confidence: 59%
“…It has been demonstrated that most n-type dopants diffuse in Ge via vacancy-mediated mechanisms [7], [8]. It was reported that phosphorus diffusivities calculated from dopant profiles produced after rapid thermal annealing were much higher than those after a long-time annealing at the same temperatures [9].…”
mentioning
confidence: 99%
“…More details of the growth conditions can be found elsewhere. [17,18] The doping concentrations of the samples are estimated by the four-point probe method and confirmed by secondary ion mass spectrometry (SIMS). The surface morphologies of the samples are analyzed by atomic force microscopy (AFM) in a tapping mode.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…. A technique gaining more and more popularity is in situ doping during CVD of epitaxial Ge layers, using PH 3 as a dopant precursor . This allows the fabrication of steep profiles, with little diffusion since typical CVD temperatures are in the range of 350–400 °C.…”
Section: Alternative Implantation Annealing and Doping Schemesmentioning
confidence: 99%